Acidentes de trabalho na medicina veterinária e como preveni-los - (:unkn) unknown (Universidade Federal do Pampa, 2017)
According to the practical experience in the Veterinary Hospital, was noticed that this profes- sion is exposed to various risks of accidents, such as physical, chemical and biological, with some of these activities being at major or minor risks. Many professionals do not protect themselves properly for certain procedures, putting their own health at risk. Concernny to the Veterinarian health, it was intended to inform clearly and objectively about the main occur- ring work accidents. Based on this, preventative actions, such as habit changes applicable in the work places forms of prevention and health preservation.
Accidents at work in veterinary medicine and how to prevent them
Keywords: Biossegurança; EPIs; Perfurocortante; Acidente de trabalho; Biosafety; PPE; Sharps waste; Work accident; CNPQ::CIENCIAS AGRARIAS